Case report – Distal tracheal injury after orotracheal intubation - Cunha, Mylena Phillipps; Graciano, Ana Carolina; Guther, Gabriela Machado; Merlos, Priscila Gabriella Carraro; Merlos, Fernando (Seven Editora, 2024)
Distal tracheal lesions resulting from orotracheal intubation are rare and more severe complications, which mainly affect females. Its cause is not specified, but it is believed to be related to direct laceration of the trachea. Thus, its diagnosis is based on the clinical symptoms observed in the patient and, for confirmation, bronchoscopy is used. Its treatment depends on the size of the lesion, for the choice of the surgical or conservative method, and should occur early. However, the site of the injury also influences the choice and effectiveness of treatment, i.e., in cases of distal tracheal injury, conservative treatment becomes impaired due to the impossibility of positioning the cuff of the orotracheal tube after the injury. Thus, the present case report aims to report and discuss the treatment of a case of distal tracheal injury after orotracheal intubation.  In addition, the scarcity of journals that address this subject shows the importance of further studies focused on the treatment of distal lesions, due to the greater complexity of this case. DOI:https://doi.org/10.56238/sevened2024.018-075